Comparative evaluation of brain neurometabolites and DTI indices following whole body and cranial irradiation: a magnetic resonance imaging and spectroscopy study. (29th August 2013) - Gupta, Mamta; Rana, Poonam; Trivedi, Richa; Kumar, B. S. Hemanth; Khan, Ahmad Raza; Soni, Ravi; Rathore, R. K. S.; Khushu, Subash
<x xml:space="preserve">Abstract</x> Understanding early differential response of brain during whole body radiation or cranial radiation exposure is of significant importance for better injury management during accidental or intentional exposure to ionizing radiation. We investigated the early microstructural and metabolic profiles using in vivo diffusion tensor imaging (DTI) and proton magnetic resonance spectroscopy (1H MRS) following whole body and cranial radiation exposure of 8 Gy in mice using a 7.0 T animal MRI system and compared profiles with sham controls at days 1, 3, 5 and 10 post irradiation. A significant decrease in fractional anisotropy (FA) values was found in hippocampus, thalamic and hypothalamic regions (p < 0.05) in both whole body and cranial irradiated groups compared with controls, suggesting radiation induced reactive astrogliosis or neuroinflammatory response. In animals exposed to whole body radiation, FA was significantly decreased in some additional brain regions such as sensory motor cortex and corpus callosum in comparison with cranial irradiation groups and controls. Changes in FA were observed till day 10 post irradiation in both the groups. However, MRS study from hippocampus revealed changes only in the whole body radiation dose group. Significant reduction in the ratios of the metabolites myoinositol (mI, p = 0.02) and taurine (tau, p = 0.03) to total creatine were observed, and these metabolic alterations persisted till day 10 post irradiation. To the best of our knowledge this study has for the first time documented a comparative account of microstructural and metabolic aspects of whole body and cranial radiation induced early brain injury using in vivo MRI. Overall our findings suggest differential response at microstructure and metabolite levels following cranial or whole body radiation exposure. Copyright © 2013 John Wiley & Sons, Ltd.